2021
DOI: 10.1186/s12935-021-01747-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SNHG3/miR-186-5p reverses the increased m6A level caused by platinum treatment through regulating METTL3 in esophageal cancer

Abstract: Background Platinum-based chemotherapy is a mainstay for treating esophageal cancer patients. In this manuscript, we have provided clues for influence of platinum on overall m6A level and further investigated the potential regulatory mechanism. Methods qRT-PCR was used to measure SNHG3 and miR-186-5p expression; ELISA and western blot were used to measure the expression of METTL3. CCK8 was used to measure the cell proliferation rate. Caspase 3/7 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Indeed, we found that the m 6 A level was much lower in patients than in HCs, demonstrating that m 6 A modification is very important in the process of NMOSD. In addition, Zhang found that altering m 6 A levels might be a novel way for improving the efficacy of platinum in cancer treatment ( Zhang et al, 2021a ), and Zhao reported that m 6 A regulation could influence the progression of lung adenocarcinoma ( Zhao and Xie, 2021 ). We hypothesized that increasing the level of m 6 A might relieve the symptoms of NMOSD, but further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the m 6 A level was much lower in patients than in HCs, demonstrating that m 6 A modification is very important in the process of NMOSD. In addition, Zhang found that altering m 6 A levels might be a novel way for improving the efficacy of platinum in cancer treatment ( Zhang et al, 2021a ), and Zhao reported that m 6 A regulation could influence the progression of lung adenocarcinoma ( Zhao and Xie, 2021 ). We hypothesized that increasing the level of m 6 A might relieve the symptoms of NMOSD, but further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG3 has been identified as a tumorpromoting lncRNA in various cancers. [33][34][35][36] Wu et al 33 found that SNHG3 was upregulated in HCC and could promote cell proliferation, migration, and invasion. Zhang et al 37 found that SNHG3 could induce epithelial-mesenchymal transition and sorafenib resistance in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study revealed that SNHG3 could epigenetically regulate its neighboring MED18 gene methylation by binding to EZH2 and inhibiting its expression in gastric cancer. 38 Besides, Zhang et al 34 found that the increased expression of SNHG3 induced by the platinum treatment could regulate the m 6 A level by targeting METTL3 in esophageal cancer. These findings indicated that the important role of SNHG3 in epigenetic regulation of cancer progression and resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It can promote tumorigeneses by epigenetically suppressing MED18 through recruiting EZH2 to methylate the MED18 neighboring region in gastric cancer (29). Recently, in a study, lncRNA SNHG3 has been shown that elevated the m6A level by binding tomiR-186-5p to increase METTL3 expression in the ESCA cells (30).…”
Section: Kaplan-meier Survival Analysis Of Differentially Expressedmentioning
confidence: 99%